Texturing of Glass Surface using Micro-slurry Jet Machining Process - Yamaguchi, Hajime; Sakata, Koshi; Kasamura, Keiji; Nakashima, Yuta; Nakanishi, Yoshitaka (Frontiers in Mechanical Engineering, 2021)
Existing methods for the microfabrication of convex structures on a glass surface require a complex and expensive masking process. In this study, a simple microfabrication method that combines the masking process using polyimide tapes and a micro-slurry jet (MSJ) process was developed. The masking process was performed using a CO2 laser machine, and the surface of the processed glass was observed using a three-dimensional laser microscope. Although the geometric shape of the mask was not a perfect circle, convex structures with a diameter of approximately 1.0 mm and heights of more than 1.5 μm were formed on soda-lime glass surfaces. The deepest structures were observed to create convex structures with a height of 16 µm. The effects of the travel speed of the nozzle and number of repetitions of the MSJ process on the height of the convex structures on the glass surface were also investigated. It was found that the masking process combining the polyimide tapes and MSJ process could form high-convexity structures on the glass surface. The proposed method is expected to allow the fabrication of novel materials and devises with various functional properties.